Interpretation of Double Movement Theory in the Case of ‘The King Of Lip Service’ - Syarif, Zalfah Alin (Journal of Islamic Communication and Counseling, 2022)
Fazlur Rahman thinking, in the contemporary Islamic world, is known as a figure who is able to convince in formulating methods to understand the Qur'an. The method brought by Fazlur Rahman in the formulation lies in the study of philosophy, social science, and humanities. The method brought by Fazlur Rahman is often referred to as double movement hermeneutics or hermeneutika gerakan ganda. The process involves repeated movements a number of times, especially the present and past problems of the contents of the Qur'an. In this study, there are two problems, how is the statement of BEM UI on the coronation of President Joko Widodo as 'The King of Lip Service' and the relevance of this to the verse of the Qur'an about keeping promises in QS. Ali 'Imran verse 77. This type of research is a study of literature with a double movement theory approach to seeking substantive matters in the law of the Qur'an regarding keeping promises. The results of this study are that leaders who do not keep their promises and are tyrannical to their people have existed since ancient times, one of which was after the leadership of the Prophet Muhammad, for example, Al-Hakim Biamrillah Al-Fathimi. Even worse, nearing the end of the world, many unjust leaders will appear. The inclusion of President Joko Widodo as The King of Lip Service is a sign of dissatisfaction with Joko Widodo's words from reality.